Diga-me com quem tu andas, então direi quem tu és: o processo de gramaticalização do então - Cavalcante, Daiane Aparecida (2018)
This research proposes an investigation and a multiplication from orality data, of the corpus linguajar from Sertão Paraíbano (2011-2012), henceforth LSP, with urban and rural paraibanos informers from the cities of Cajazeiras, Catingueira, Catolé do Rocha, Conceição, Itaporanga, Patos, Pombal, Sousa and Princesa Isabel. The research that we present is based on the functionalist theorist, who considers language as a dynamic phenomenon, in which the grammar is conceived as an adaptive and emergent system. In this perspective, grammaticalization studies will be considered, especially the principles formulated by Hopper (1991) and the motivational mechanisms of grammaticalization postulated by Bybee (1994). These motivating principles and mechanisms will be applied to verify the stage of grammaticalization, which we can find the object of study. After a data analysis, the results indicate that the item follows the unidirectional scale adverb> conjunction> discourse marker, proceeding not between the limits of Discourse and Grammar. Regarding the stage of grammaticalization, we find that the item is in the middle stage of grammaticalization, not being decategorized, so it does not totally lose the prototypical traits of its function, the semantic fading, the semantic neutralization of the item is partial, in this way presents slippery and fluid behavior. There is a loss of semantic transparency, but the meta / target function does not erase or cancel the emergence of other divergent functions of the item, which keeps the traits of the source category unharmed. Therefore, there are more pragmatic discursive gains than losses. Thus, we prove that what happens is the coexistence and the harmonious coexistence between the two functions: source-function and target/meta function, which shows the partial stage of grammaticalization of the item.